Characteristics of the intestinal flora of specific pathogen free chickens with age. (July 2019) - Xi, Yu; Shuling, Niu; Kunyuan, Tie; Qiuyang, Zhang; Hewen, Deng; ChenCheng, Gao; Tianhe, Yu; Liancheng, Lei; Xin, Feng
Abstract: Specific pathogen-free (SPF) experimental animals are recognized as standard laboratory animals in the fields of biomedical, animal husbandry and veterinary research and production. Intestinal flora plays a critical role in nutrient absorption, improving health and protecting the host from pathogens. We therefore explored the variation and maintenance of intestinal flora in SPF chicks in order to better understand the composition of intestinal microflorain SPF chickens, and provide reference for the study of intestinal flora of SPF experimental animals. Five chicks were randomly selected at each of 14, 28, and 42 days, and ceca were removed for DNA extraction. The Illumina Miseq platform was used for microbiome analysis of the V3–V4 region of the 16S rRNA gene. During the course of chick gut microbiome development, we observed major changes in diversity, especially between day 14 and day 28. Firmicutes, Proteobacteria, and Bacteroidetes were the main bacterial taxa, and Firmicutes increased significantly with age. The genus with the highest relative abundance was Lactobacillus, followed by Faecalibacterium . In addition, while abundance of Ruminococcaceae spp., Ruminococcus, and Blautia increased with age, Lactobacillus, Enterobacteriaceae spp., and Oscillospira decreased with age. Interestingly, the abundance of Faecalibacterium first increased and then decreased over time. The characteristics of SPF chicken gut flora at different ages establish a basis for the regulation of intestinal flora in the early stage of brooding, and also provide a theoretical foundation for controlling and preventing infections and poultry diseases in newborn chickens. Highlights: 14–28 days is the key period for the establishment of SPF chicken intestinal flora. The dominant bacteria were Firmicutes, Proteobacteria, and Bacteroidetes. Butyricicoccus and Dorea producing butyric acid increase with age.